2008
DOI: 10.1007/s10695-008-9287-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth hormone (GH), growth hormone receptor (GHR), and insulin-like growth factor I (IGF-I) gene transcription after hyperosmotic stress in the Brazilian flounder Paralichthys orbignyanus

Abstract: Growth hormone (GH) action is the result of an intracellular cascade initiated just after its interaction with the growth hormone receptor (GHR) located on the surface of target cells. This cascade culminates with the transcription of target genes, such as the insulin-like growth factors (IGFs), which are responsible for most GH biological effects. In addition to its central role in growth, fish GH is also involved with osmoregulatory control. Within this context, the objective of the present work was to isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
1
10
0
2
Order By: Relevance
“…Two observations are interesting to note in this context. First, hyperosmotic stress increased growth hormone-mediated, hepatic insulin-like growth factor 1 production (Meier et al 2009), which may have increased pituitary gnrhr mRNA levels (Luckenbach et al 2010). Secondly, hyperosmotic stress following SW exposure might also have stimulated vasopressin release (Balment et al 2006), which in turn can directly stimulate testicular androgen release (Rodríguez & Specker 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Two observations are interesting to note in this context. First, hyperosmotic stress increased growth hormone-mediated, hepatic insulin-like growth factor 1 production (Meier et al 2009), which may have increased pituitary gnrhr mRNA levels (Luckenbach et al 2010). Secondly, hyperosmotic stress following SW exposure might also have stimulated vasopressin release (Balment et al 2006), which in turn can directly stimulate testicular androgen release (Rodríguez & Specker 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The isosmotic point estimate for P. orbignyanus is 10.9‰ (SAMPAIO; BIANCHINI, 2002), the salinity likely to be found in a brackish coastal lagoon such as "Laguna de Rocha" (CONDE et al, 2000). However, it is also known that in P. orbignyanus, as in other species, growth hormone levels increase after suffering hyperosmotic stress, whereby the highest growth rates in P. orbignyanus would be obtained in seawater (MEIER et al, 2009). Despite this, SAMPAIO et al, 2001 observed no significant variations in the growth rates of P. orbignyanus cultured at salinities such as 30ppt and 11ppt.…”
Section: Paralichthys Orbignyanus Paralichthys Patagonicusmentioning
confidence: 99%
“…Estudos recentes relacionados à larvicultura (Sampaio et al, 2007), reprodução (Lanes et al, 2008;Sampaio et al, 2008), potencial para transgênese (Lanes et al, 2009) e expressão de genes ligados ao crescimento e ao controle da fome (Meier et al, 2009;Campos et al, 2010) demonstram a viabilidade do cultivo desta espécie. No entanto, ainda não há estudos sobre os mecanismos moleculares e fisiológicos sobre o controle da puberdade nesta espécie.…”
Section: Diversos Estudos Têm Demonstrado Que O Conhecimento Dos Aspeunclassified
“…Para densidade óptica das bandas, usou-se o software TotalLab TL 100 (Nonlinar Dynamics, Inglaterra). A taxa de densidade óptica sbGnRH/β-actina foi utilizada para o cálculo de expressão gênica, segundo Meier et al (2009).…”
Section: *Primers Degenerados: M (A + C) W (A + T) R (A + G) K (T unclassified